Processing of Coal into Coke with the Pyrolysis Method - Nurdin, M Ilham; Damayanti, Jeanne Dewi (Politeknik Negeri Ujung Pandang, 2023)
Utilization of coal as a direct fuel can cause environmental problems such as solid waste in the form of fly ash (flyash). This study aims to process coal into coke using the pyrolysis method in the hope of increasing the quality and efficiency of coal that is safe for the environment. This research was conducted in 3 stages. The first stage was carried out by crushing coal, sieving coal, testing proximate and ultimate coal, and analyzing the calorific value of coal. The second stage is carried out by preparing coal, pyrolysis of coal using a set of pyrolysis tools. Pyrolysis was operated at Â± 400oC using a stainless reactor with a reactor volume capacity of 16 liters. Pyrolysis is carried out until no more liquid smoke is produced. The third stage was carried out by crushing the coke product, testing the proximate and ultimate coke (moisture content, ash content, volatile matter, fixed carbon, total sulfur), and analyzing the calorific value of the coke. The results showed that the quality of coal could be improved by processing it into coke using the pyrolysis method as evidenced by a decrease in water content, a decrease in volatile matter, an increase in fixed carbon, and an increase in calorific value